Konsep fundamental matematika pada tenun songket siak - Auliani, Antin; Suripah, Suripah (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2024)
Along with the times, cultural values among the community, including students, are fading. An alternative that can be done is to preserve culture and reintroduce it through the formal education curriculum. So it is necessary to conduct this research with the aim of describing the fundamental mathematical concepts contained in Siak songket woven fabrics. This study uses a descriptive qualitative method. The respondents in this study are the owner of the Siak weaving industry, Mrs. Atun permai. The data collection techniques used in this study are observation, interviews and documentation. The data analysis technique is carried out through 4 stages, namely data collection, data reduction, data presentation and conclusion drawn. The results of this study show that the motif of Siak songket woven fabric comes from animals, plants, and celestial bodies and contains meanings, philosophies and mathematical ideas such as geometric transformations, units of time and social arithmetic concepts. Several mathematical concepts contained in Siak sticky woven fabric can be applied to contextual mathematics learning to make it easier to understand mathematical concepts and associate culture into mathematics learning.